Food Rations at Ebla: A Preliminary Account on the Ration Lists Coming from the Ebla Palace Archive L. 2712 - Milano, Lucio
1. The Ebla Archive L. 2712. 2. Typology of the Lists. 3. Capacity Measures and Numerical Fractions. 4. Structure of the Accounting: A Case of Complex Procedure. 5. Historical Value and "Reliability" of the Ration Lists. 6. Recipients and Amount of the Rations. 7. Rations and Volumes: The Value of the SÌLA at Ebla. 8. Final Observations